A review of the legal work of Joaquin Costa in the dawn of the 21st century: the trace of costumary Law in the Aragon Regional Law code - Bernar Mainar, Rafael (Revista de derecho aragonés, 2021)
Among the different scenarios cultivated by Joaquin Costa (history, literature, geography, pedagogy, anthropology, agriculture, economics, politics or law), his most outstanding contribution is, undoubtedly, that of the legal field, stained with a clear sociological component.Costa was a strong defender of customary law, especially with regard to Aragonese law, as evidenced by his extensive written work on the subject. Good proof of its influence in this matter is that the current Aragonese law collects, to a large extent, its legal thinking, which allows us to re-read it in the XXI century, based on the regulation contained in the Aragon Regional Law Code (ARLC).
Keywords: Joaquín Costa; customary law; positive law; Aragonese civil law; Aragon regional law code (ARLC)